(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
By delving deeply into the core mind set or state of mind of the individual committing crime, the notion of crime and criminology may be grasped. This article also discusses the motives for the crime and the variables that influence a person’s decision to commit a crime. It also covers the idea of crimes and the different regulations that have been established for the commission of certain offenses. This page also covers a variety of criminology ideas that have been classified according to the MENS REA that led to the crime. Apart from that, this article also discusses the many sorts of offenses that have been recognized by the law. What is crime, in its most basic form? What are the elements that lead to criminal activity? What are the various punishments that have been established for various crimes? What are the several courts that have jurisdiction over criminal cases? What special criminal provisions have been established in the jurisdiction? All of these debates have been covered in this article. This article also covers the fundamentals of criminology and the different components that contribute to the definition of the term. The idea of criminology has been separated into two sections in this article: one half discusses the reasons that lead to a victim being a victim, and the other portion discusses the variables that lead to a person becoming an offender. Aside from crime and criminology, this article discusses the different responsibilities and capabilities of criminal courts, which are critical in establishing what constitutes a crime and dealing with criminal cases.